2016
DOI: 10.1186/s40478-016-0324-5
|View full text |Cite
|
Sign up to set email alerts
|

The ALS/FTLD associated protein C9orf72 associates with SMCR8 and WDR41 to regulate the autophagy-lysosome pathway

Abstract: Hexanucleotide repeat expansion in the C9orf72 gene is a leading cause of frontotemporal lobar degeneration (FTLD) with amyotrophic lateral sclerosis (ALS). Reduced expression of C9orf72 has been proposed as a possible disease mechanism. However, the cellular function of C9orf72 remains to be characterized. Here we report the identification of two binding partners of C9orf72: SMCR8 and WDR41. We show that WDR41 interacts with the C9orf72/SMCR8 heterodimer and WDR41 is tightly associated with the Golgi complex.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

33
306
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 257 publications
(347 citation statements)
references
References 56 publications
(67 reference statements)
33
306
2
1
Order By: Relevance
“…We observed a relative increase in LC3I levels upon loss of C9orf72 (S2 Fig), in consistence with a recent report for LC3 levels in C9orf72 KO mouse liver and spleen tissues [39], which we interpret as an increase in autophagosome turnover instead of a decrease in LC3II formation. In support of this model, we did not observe a decrease in LC3II levels after Bafilomycin treatment under full nutrient conditions, suggesting that the formation of LC3II is intact (S3 Fig).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We observed a relative increase in LC3I levels upon loss of C9orf72 (S2 Fig), in consistence with a recent report for LC3 levels in C9orf72 KO mouse liver and spleen tissues [39], which we interpret as an increase in autophagosome turnover instead of a decrease in LC3II formation. In support of this model, we did not observe a decrease in LC3II levels after Bafilomycin treatment under full nutrient conditions, suggesting that the formation of LC3II is intact (S3 Fig).…”
Section: Discussionsupporting
confidence: 92%
“…There have been recent reports describing C9orf72’s functions in autophagy [39, 4143], including a decrease in autophagy initiation as a result of knockdown of C9orf72 [41, 42]. These observations are not necessarily mutually exclusive to our present study.…”
Section: Discussionsupporting
confidence: 60%
“…Although studies in mice have indicated that C9orf72 activity is important for myeloid cell function 14,18 , a report in mouse neurons and zebrafish suggests that C9orf72 isoform A may modulate poly-Q Ataxin-2 toxicity 20 , and studies have implicated C9ORF72 in regulating autophagy 20,31,32,38 , our study provides the first direct evidence showing that gain- and loss-of-function C9ORF72 mechanisms cooperate to cause the degeneration of human motor neurons. Recent studies have shown that C9ORF72 isoform A, but not isoform B, can form a functional complex with SMCR8 and WDR41 20 .…”
Section: Discussionmentioning
confidence: 64%
“…Progranulin (PGRN) is localized to lysosomes through at least two independent trafficking pathways . Although the role of C9orf72 protein is unclear, it is believed to be implicated in membrane trafficking and autophagy . Furthermore, while heterozygous loss of function mutations in GRN cause FTLD‐TDP , homozygous mutations in GRN cause a lysosomal storage disorder known as neuronal ceroid lipofuscinosis (NCL) .…”
Section: Introductionmentioning
confidence: 99%